Table of Contents - Board, Editorial (Law, State and Telecommunications Review, 2021)
Dear Reader, We are pleased to present the first issue of the thirteenth volume of the Law, State and Telecommunications Review (LSTR). In this issue, the journal publishes a number of original articles on topics relevant to digital rights and to information and communications technologies in different parts of the world from a myriad of interdisciplinary perspectives. We are delighted to include articles on the perception of the right to Internet access in the information society, the participation of minors in interactive softwares, the role of regulators in collaborative regulatory systems, the legal aspects of blockchain technology in Colombia, especially with regard to public faith, privacy and data protection, the recognition of privacy and personal data protection as species of consumer rights in Nigeria, the right to access to public information in the Arab States, the role of mass media in preventing corruption in Ukraine, and the experience of the supreme courts in Colombia and Brazil with Artificial Intelligence (AI). We hope you will enjoy reading this issue, and we look forward to a second issue to be released on October 2021. Sincerely, Prof. Alessandra Silveira Prof. Alexandre Veronese Guest Editors, The Law, State and Telecommunications Review